Effect of Resistance Training and Mindfulness on Erectile Dysfunction in Addicts Who Were Quitting Addiction - Moslem Safdariyan Dehkordi; Moslem Safdariyan Dehkordi1; Farzaneh Thaghian (Shiraz University of Medical Sciences, 2019)
Background: Addiction is one of the greatest problems of human societies, which not only causes social and behavioral disorders but also affects different aspects of health and imposes huge financial loss on individuals, families, and society. The purpose of this study was to determine the effect of resistance training and mindfulness on the sexual function of addicted people. Methods: The present study is an experimental research conducted using a pretest-posttest design with a control group. Participants of this study consisted of 50 married men aged 30-45; since their referral to addiction treatment centers in Shahrekord two weeks had passed. They were selected using convenience sampling method and matched based on the age range and history of addiction and divided into four groups of resistance training, mindfulness, combined (resistance training and mindfulness), and control. The resistance and combined training groups participated in resistance training for 8 weeks. The mindfulness and combined training groups participated in mindfulness therapy training for 8 weeks. During this period, the control group performed their daily activities. Before and after the intervention, data were collected using an erectile dysfunction questionnaire. Data were analyzed using covariance. Results: All three types of intervention, including resistance training (P≤0.001), mindfulness training (P≤0.006), and combined training (P≤0.001), lead to the improvement of sexual performance. Additionally, combined training was more effective compared to the other two methods (P≤0.001). Conclusion: In order to improve the sexual performance of addicts, physical exercise and mindfulness training can be used. The simultaneous use of both methods has a greater influence on the improvement of sexual performance due to the addicts benefitting from the effects of two types of intervention.